Improving Simple Narrative Essay Writing Skills Using Glowing Image Media in Class II Elementary School Students - Silitonga, Immanuel Doclas Belmondo; Sibarani, Imelda Sabrina (Jurnal Ilmu Sosial Mamangan, 2025)
This research aims to (1) find out the pre-cycle results of students in writing simple essays, (2) find out the results of learning completeness in cycle I in writing simple essays using serial image media, and (3) find out the results of learning completeness in cycle II in writing simple essays using serial image media. This research was carried out in September 2023 - November 2023. This research used a descriptive method with a quantitative type of research. This research applies a pre-cycle process, cycle I and cycle II. The data collection methods used in this research were documentation, observation, interviews and tests. After all the data is collected, it is continued with the data analysis method, namely quantitative descriptive research. The research results concluded that (1) student learning outcomes increased significantly through several stages, pre-cycle, cycle I and cycle II; and (2) student learning outcomes per cycle experienced an increase in learning improvements where in the pre-cycle there were 8 students who completed with a percentage of 29.62%, in the first cycle there were 10 students who completed with a percentage of 37.03%, and in the second cycle there were 24 students which completed with a percentage of 88.88%, where an average score of 80.85 was obtained from 27 students.